Implementation of Apnea Monitor with Telemedicine Smartphone System (TMSS) for diagnosis and management of sleep-disordered breathing in Cases of Respiratory Disorders in Indonesia - I Dewa Gede Hari Wisana; Her Gumiwang Ariswati; Lusiana Lusiana; Farid Amrinsani (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
In connection with the increase in patients with respiratory problems in the Kenjeran Health Centre area of Surabaya City and the cases of respiratory problems in Covid 19 patients which caused a lack of treatment for these patients due to limited health workers and insufficient monitoring equipment, resulting in an impact on the health service system for patients being disrupted. The Community Service Programme with the PKM scheme is carried out in the form of synergistic cooperation between the Poltekkes Kemenkes Surabaya and the Surabaya City Health Office which is oriented towards community independence through counseling and mentoring, especially in the application of the use of Apnea Monitor at the respiration rate using the Telemedicine Smartphone System (TMSS). These problems are obtained from supporting data about the general description, health degree situation, health resource situation, health service efforts and disease cases at the Kenjeran Health Centre obtained from the Surabaya City Community Satisfaction Survey 2016-2021 so that they can be analysed for problem solutions. With the concept of methodology, a design / flow of extension activities and assistance in the application of the use of Apnea Monitor with Telemedicine System carried out by a team consisting of 3 lecturers and 3 students in accordance with their fields of expertise as well as participants from Kenjeran Health Centre and the community in the area, so that the Community Service activities to be carried out are expected to help solve the problems faced by Kenjeran Health Centre. The results of activities that have been achieved are: 1).The results of SPO2 and BPM values on 40 workers are recorded.2). Identification of 40 workers who do not experience respiratory problems; 3). Identification of workers with respiratory problems (none); 4) Implementation of the TMSS apnea monitor system by measuring SPO2 and BPM in smoking workers in the Kenjeran Health Centre area. Future development plans for the Apnea Monitor -TMSS tool can be accessed via the web.